Long-term green-Mediterranean diet may favor fasting morning cortisol stress hormone; the DIRECT-PLUS clinical trial - Alufer, Liav; Tsaban, Gal; Rinott, Ehud; Kaplan, Alon; Meir, Anat Yaskolka; Zelicha, Hila; Ceglarek, Uta; Isermann, Berend; Blüher, Matthias; Stumvoll, Michael; Stampfer, Meir J.; Shai, Iris (Frontiers in Endocrinology, 2023)
Background: Fasting morning cortisol (FMC) stress hormone levels, are suggested to reflect increased cardiometabolic risk. Acute response to weight loss diet could elevate FMC. Richer Polyphenols and lower carbohydrates diets could favor FMC levels. We aimed to explore the effect of long-term high polyphenol Mediterranean diet ( green-MED) on FMC and its relation to metabolic health.We randomized 294 participants into one of three dietary interventions for 18months: healthy dietary guidelines (HDG), Mediterranean (MED) diet, and Green-MED diet.Both MED diets were similarly hypocaloric and lower in carbohydrates and included walnuts (28 g/day). The high-polyphenols/low-meat Green-MED group further included green tea (3-4 cups/day) and a Wolffia-globosa Mankai plant 1-cup green shakeFMC was obtained between 07:00-07:30AM at baseline, six, and eighteen-months.Results: Participants (age=51.1years, 88% men) had a mean BMI of 31.3kg/m 2 , FMC=304.07nmolŁ, and glycated-hemoglobin-A1c (HbA1c)=5.5%; 11% had type 2 diabetes and 38% were prediabetes. Baseline FMC was higher among men (308.6±90.05nmolŁ) than women (269.6± 83.9nmolŁ;p=0.02). Higher baseline FMC was directly associated with age, dysglycemia, MRI-assessed visceral adiposity, fasting plasma glucose (FPG), high-sensitivity C-reactive-protein (hsCRP), testosterone, Progesterone and TSH levels (p≤0.05 for all). The 18-month retention was 89%. After 6 months, there were no significant changes in FMC among all intervention groups. However, after 18-months, both MED groups significantly reduced FMC (MED=-1.6%[-21.45 nmol/L ]; Green-MED=-1.8%[-26.67 nmol/L]; p<0.05 vs. baseline), as opposed to HDG dieters (+4%[-12 nmol/L], p=0.28 vs. baseline), whereas Green-MED diet FMC change was significant as compared to HDG diet group (p=0.048 multivariable models). Overall, 18-month decrease in FMC levels was associated with favorable changes in FPG, HbA1c, hsCRP , TSH, testosterone and MRIassessed hepatosteatosis, and with unfavorable changes of HDLc (p<0.05 for all, weight loss adjusted, multivariable models).Conclusions: Long-term adherence to MED diets, and mainly green-MED/high polyphenols diet, may lower FMC, stress hormone, levels,. Lifestyle-induced FMC decrease may have potential benefits related to cardiometabolic health, irrespective of weight loss.